Chapter 7 Becoming "Chinese" in Southeast Asia - Hau, Caroline S. (Taylor & Francis, 2017)
China's rise and processes of Sinicization suggest that recombination of new and old elements rather than a total rupture with or return to the past is China's likely future. In both space and time, civilizational politics offers the broadest social context. It is of particular salience in China. Reification of civilizations into simple categories such as East and West is widespread in everyday politics and common in policy and academic writings. This book's emphasis on Sinicization as a specific instance of civilizational processes counters political and intellectual shortcuts and corrects the mistakes to which they often lead. Sinicization illustrates that like other civilizations China has always been open to variegated social and political processes that have brought together many different kinds of peoples adhering to very different kinds of practices. This book tries to avoid the reifications and celebrations that mark much of the contemporary public debate about China's rise. It highlights instead complex processes and political practices bridging East and West that avoid easy shortcuts. The analytical perspectives of this book are laid out in Katzenstein's opening and concluding chapters. They are explored in six outstanding case studies, written by widely known authors, which over questions of security, political economy and culture.